Novos agentes históricos da Reserva Indígena de Dourados (RID) : territorialidades, identidades culturais e desafios dos Kaiowa em viver a plenitude do seu Ñande Reko - Falcão, Raul Claudio Lima (2022)
ABSTRACT: In recent years inhabitants of RID use practices that did not belong to their daily lives and to traditional knowledge, those that were built, secularly, from conceptions and temporalities inherited from their ancestors. In this direction, the present research work has as object of study the actions and practices carried out by new agents, inhabitants of the Golden Indigenous Reserve, who act with the purpose of resisting and preserving the cultural identify of the Kaiowa people who reside there. Our hypothesis is that these agents use practices and expedients of urban space to propagate their way of life beyond the indigenous reserve, that is, they transpose the "belt" built around IT to occupy other territories (in some cases virtual) with a view to strengthening and sustaining your ñande reko, way of being, as well as to present sustainable and innovative ways of practicing your agricultural craft and thus sustain yourself economically. In a way, we perceive through our analysis that knowledge has been dynamicized, appropriated and incorporated by people from the community who, through a creative and innovative movement, seek to preserve the Kaiowa identity connected to the challenges imposed on the ethnic collective today, mainly due to the coexistence with the non-indigenous society that resides in the municipality of Dourados-MS.